Efficacy and Safety of Wuling Capsule Combined with Fupentixol and Melitracen Tablets in Active Ulcerative Colitis Patients Accompanied with Anxiety and Depression - MO Dayu, LIU Yingchao, WANG Feida, NI Siyi, SHEN Yan (Zhongguo quanke yixue, 2022)
BackgroundPsychotherapy is an important component of the treatment program for inflammatory bowel disease (IBD) , a common chronic incurable digestive system disease accompanied with psychosomatic disorder, which involves ulcerative colitis (UC) . Wuling capsule has proven to be effective in multiple gastrointestinal diseases with psychosomatic disorders, but there are rare studies about its effect on improving the condition, anxiety and depression of UC patients.ObjectiveTo investigate the efficacy and safety of Wuling capsule with Fupentixol and melitracen tablets in active UC patients with anxiety and depression.MethodsA total of 120 active UC patients with anxiety and depression were selected from Gastroenterology Clinic or Inpatient Department of the Second Affiliated Hospital of Zhejiang Chinese Medical University and Zhejiang Provincial Tongde Hospital from January 2019 to December 2020, and equally, double-blindly randomized into control group, Deanxit group, Wuling capsule group and combination group, receiving Mesalazine sustained-release tablets (hereinafter referred to Mesalazine) , Mesalazine with Fupentixol and melitracen tablets, Mesalazine with Wuling capsules, Mesalazine with Fupentixol and melitracen tablets and Wuling capsules, respectively. All of the four groups were treated for 8 consecutive weeks as a course. Pre- and post-treatment main clinical symptom score, modified Mayo score, inflammatory response indicators, Zung Self-rating Anxiety Scale (SAS) score, Zung Self-rating Depression Scale (SDS) score, and Inflammatory Bowel Disease Questionnaire (IBDQ) score were compared across the four groups. Meanwhile, safety evaluation for the four treatments was conducted.ResultsFinally, 113 cases (except Wuling capsule group containing 29 cases, other three groups containing 28 cases) who completed this study were included for analysis. Compared with other three groups, combination group showed lower post-treatment diarrhea score, mucus with blood and pus in stools score, abdominal pain score and total score of clinical symptoms, modified Mayo score, erythrocyte sedimentation rate, serum levels of C-reactive protein, tumor necrosis factor-α and interleukin-6, as well as SAS and SDS scores, and higher scores of bowel, systemic, emotional and social domains and total IBDQ score (P<0.05) . One control group case had abdominal distension and one Deanxit group case had hyposomnia during treatment, but were spontaneously relieved.ConclusionIn active UC patients accompanied with anxiety and depression, Wuling capsule with Fupentixol and melitracen tablets could relieve the clinical symptoms, severity of condition, inflammatory response, anxiety and depression disorders, improve the quality of life, with relatively high safety. Therefore, Wuling capsule may be a choice for optimizing the comprehensive treatment plan of UC.